2018
DOI: 10.1016/j.jval.2017.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis of Abatacept Compared with Adalimumab on Background Methotrexate in Biologic-Naive Adult Patients with Rheumatoid Arthritis and Poor Prognosis

Abstract: Abatacept is a cost effective alternative to adalimumab in patients with RA with high ACPA levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 37 publications
(74 reference statements)
0
17
0
1
Order By: Relevance
“…Incorporation of subgroups based on prognostic factors ranked high on the prioritization order as this is relatively straightforward. In addition, recent cost effectiveness analyses have demonstrated the importance of incorporation of subgroups as these patients may have characteristics which are potentially effect modifiers [ 29 , 30 ]. However, these analyses are still limited and further work needs to be done to understand and define RA subgroups with combinations of prognostic factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Incorporation of subgroups based on prognostic factors ranked high on the prioritization order as this is relatively straightforward. In addition, recent cost effectiveness analyses have demonstrated the importance of incorporation of subgroups as these patients may have characteristics which are potentially effect modifiers [ 29 , 30 ]. However, these analyses are still limited and further work needs to be done to understand and define RA subgroups with combinations of prognostic factors.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of these models do not report incremental cost-effectiveness ratios (ICERs) according to important subgroups. Recent studies have evaluated ICER within a limited number of RA subgroups [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are some clinical studies that directly compared abatacept with adalimumab (both on background treatment with methotrexate), which indicate some benefits of abatacept over the TNF-α inhibitor [273][274][275]: two AMPLE studies (Abatacept versus Adalimumab Comparison in Biologic-Naïve RA Patients with Background Methotrexate) showed that the overall disease outcome, improvement on tender and swollen joint count (69.4% ± 2.9% improvement in swollen joint count for abatacept vs. 69.3% ± 2.9% for adalimumab), physician's global assessment (63.6% ± 4.8% for abatacept vs. 62.8% ± 4.7% for adalimumab), CRP levels, pain (mean ± SEM improvements in pain at year 2: 53.7% ± 6.2% for abatacept vs. 38.5% ± 6.1% for adalimumab), fatigue, as well as ability to perform both work and daily activities were comparable between abatacept and adalimumab [273,274]. Moreover, the improvement in ACR50 response rates over 2 years was also similar (44.7% for abatacept vs. 46.6% for adalimumab) [274].…”
Section: Inhibitors Of Co-stimulationmentioning
confidence: 99%
“…However, there were less discontinuations in the abatacept group compared with adalimumab due to adverse effects (3.8% for abatacept vs. 9.5% for adalimumab), a lower frequency of serious adverse events (1.6% vs. 4.9%) and severe infections (0/12 vs. 9/19 patients), as well as reduced occurrence of injection site reactions (4.1% vs. 10.4%) [274]. Economically, abatacept was suggested to be a cost-effective alternative to adalimumab in patients with higher ACPAs by Alemao and colleagues after analyzing 646 randomized patients treated with either abatacept or adalimumab (both in combination with methotrexate treatment) [275].…”
Section: Inhibitors Of Co-stimulationmentioning
confidence: 99%
“…Treatment strategies include pain-relieving drugs and anti-inflammatory medications that slow joint damage, combined with physical therapies that involve a well-balanced sequence of rest and exercise. In view of better compliance, exercise programs are highly personalized and tailor-made under consideration of the patients' physical abilities, limitations, and needs; [6,7]. It has been reported that RA patients have an increased risk of experiencing functional disability with the prolongation of the course of disease [8].…”
Section: Introductionmentioning
confidence: 99%